2011
DOI: 10.1177/1352458511424903
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine mapping in cerebrospinal fluid and blood in multiple sclerosis patients without oligoclonal bands

Abstract: OCB- MS patients do not seem to constitute a separate entity concerning inflammatory parameters measured as cytokine concentrations in CSF and blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 10 publications
5
10
0
Order By: Relevance
“…Consequently elevated levels of sCD14 may suggest only a transitory macrophage activation limited to attacks. The lack of consistent difference of sCD14 levels between oligoclonal band positive and negative patients are in line with our results that sCD14 does not appear as a reliable inflammatory marker (Vrethem et al, 2011). Moreover Walter et al, reported no significant increase in either systemic or intrathecal release of sCD14 in MS patients, as compared to controls, regardless of the presence or absence of active disease (Walter et al, 2006).…”
Section: Discussionsupporting
confidence: 87%
“…Consequently elevated levels of sCD14 may suggest only a transitory macrophage activation limited to attacks. The lack of consistent difference of sCD14 levels between oligoclonal band positive and negative patients are in line with our results that sCD14 does not appear as a reliable inflammatory marker (Vrethem et al, 2011). Moreover Walter et al, reported no significant increase in either systemic or intrathecal release of sCD14 in MS patients, as compared to controls, regardless of the presence or absence of active disease (Walter et al, 2006).…”
Section: Discussionsupporting
confidence: 87%
“…In adult patients with multiple sclerosis, no cytokine differences were found based on presence or absence of OCB (Maimone et al, 1991). In another group of adults with multiple sclerosis, the concentrations of 13 cytokines were similar in OCB(+) and OCB(−) patients (Vrethem et al, 2012). The authors concluded that OCB(−) patients did not seem to constitute a separate entity concerning those inflammatory parameters, which they interpreted as supporting a mainly T-cell-driven mechanism Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Abbreviations: CSF, cerebrospinal fluid; OCB, oligoclonal bands; ns, not statistically significant. (Vrethem et al, 2012), but they queried as to whether results for BAFF or CXCL13 might be different. In untreated optic neuritis, six cytokines did not discriminate between OCB(+) and OCB(−) patients (Kivisäkk et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amyotrophic lateral sclerosis Serum: IL-6, IL-13, IL-17, TNF-α, MCP-1, CRP CSF: IFNγ Tissue: Translocator protein upregulation [20][21][22][23][24] [25] [26] Alzheimer's disease Serum: IL-6, IL-1β, TNF-α, CRP, TGF-β, IL-12, IL-18 CSF: TGF-β Tissue: Translocator protein upregulation [27,28] [27] [17] Huntington's disease Serum: IL-6, IL-8, IL-13, TNF-α CSF: IL-6, IL-8 Tissue: Translocator protein upregulation [29] [30] [31] Multiple sclerosis Serum: TNF-α, IFNγ, IL-1β, IL-6, IL-10, CXCL8, TGF-β CSF: TNF-α, IL-1β Tissue: Translocator protein upregulation [32,33] [34] [16] Parkinson's disease Serum: MCP-1, RANTES, MIP-1α, IL-8, IFNγ, IL-1β, TNF-α CSF: IL-1β, IL-6 Tissue: Translocator protein upregulation [35] [36] [18] II. NEURODEGENERATIVE DISORDERS…”
Section: Disease Detectable Inflammatory Markers Sourcesmentioning
confidence: 99%